The Effectiveness of Plyometric and Agility Ladder on Increasing Leg Muscle Power and Reaction Speed - Priyanto, Andy Bima; Mukti Widodo, Haryo; Himawan, Agus; Putri Purwoto, Septyaningrum; Yuli Handayani, Heni (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
Leg muscle power and reaction speed are important components in athlete performance, especially in sports that require explosive movements such as sprinting, jumping, and rapid changes of direction. The purpose of this study was to assess the effectiveness of a combination of plyometric and agility ladder training on increasing leg muscle power and reaction speed, especially in futsal players. Both types of training are theoretically capable of increasing explosive ability and motor response speed. The method used was a quasi-experimental study with a pre-test and post-test design. The results showed that there was a significant increase in both physical variables studied. These findings support the use of combined training as an efficient method for developing the physical condition of futsal athletes.